PERAN TERJEMAH DALAM KEBUDAYAAN DAN PERSOALAN IDENTITAS - Khairon Nahdiyyin (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
This paper aims at elaborating the relationship of translation, culture, and identity. Translation is one means of cultural development. It adopts not only from other elements, but also from other culture to be dialogued and equivalented with the target culture. Within this "taking" and "giving" process the identity of a culture is laid. Historically speaking, translation has proved its great role in human civilization since Ancient Greek. Through translation the contact between two cultures can benefit one another in many ways. This contact involves at least two processes; dialogue of language and of thought. One critical issue in terms of cultural development, which is found through out history, is that translation involved a nation in the process.